Comparing Two Alcohol Screening Measures on Rates of Risky Alcohol Use in a University Health Clinic - McCabe, Brian (2019)
College drinking is a serious health concern. Few studies have examined screening measures and methods of administration. This study compares two alcohol screens (NIAAA 5/4 binge drinking question or Alcohol Use Disorders Identification Test (AUDIT)) in a college student health clinic waiting room and two modes of administration (self-administered either on a computer kiosk or on a tablet computer). Participants were 259 undergraduates from the University of Miami. Most (78–98%) students completed screening. More students were identified with risky alcohol use with the 5/4 (49%) than AUDIT (14%). On the 5/4, administration method was not linked to completion, 93% kiosk vs. 95% tablet, p = .554, but was related to identification as a risky alcohol user, 42% kiosk vs. 56% tablet, p = .033. On the AUDIT, administration method was significantly related to completion, 73% kiosk vs. 98% tablet, p < .001, and identification, 8% kiosk vs. 23% tablet, p = .003. Method of administration of the single item 5/4 binge drinking question was related to the a higher proportion of students identified with risky alcohol use when screened by a computer tablet, but not completion rates; the AUDIT method of administration was related to both completion and identification rates (higher rates with the tablet in both cases). Education of student health providers who make decisions about what screening tools to use in their centers and who interpret the results of alcohol screening in college health centers should consider the potential influence of administration method. Future research should examine the reasons that method of administration might influence screening results.